1996
DOI: 10.1093/rheumatology/35.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Slicc/Acr Damage Index Is Valid, and Renal and Pulmonary Organ Scores Are Predictors of Severe Outcome in Patients With Systemic Lupus Erythematosus

Abstract: SUMMARYWe investigated the Systemic Lupus International Collaborative Clinics/American College of Rheumatology (SLICC/ACR) Damage Index as a predictor of severe outcome and an indicator of morbidity in different ethnic groups, and in regard to its validity. We retrospectively studied disease course within 10 yr of diagnosis in an inception cohort of 80 patients with systemic lupus erythematosus (SLE). The mean renal damage score (DS) at 1 yr after diagnosis was a significant predictor of endstage renal failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
141
5
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(163 citation statements)
references
References 15 publications
11
141
5
6
Order By: Relevance
“…The explanation for these differences remains to be elucidated. In contrast to data published by other investigators, our patients have not accrued significant musculoskeletal damage (40)(41)(42)(43)(44)(45), only 12% overall. The inclusion of the Hispanic subset in our LUMINA cohort is probably not the explanation for this finding, since high frequencies of musculoskeletal damage have been reported for cohorts consisting solely of Hispanic patients (as well as for cohorts consisting solely of African American and Caucasian patients), and the frequency of musculoskeletal problems did not differ very much among ethnic groups in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The explanation for these differences remains to be elucidated. In contrast to data published by other investigators, our patients have not accrued significant musculoskeletal damage (40)(41)(42)(43)(44)(45), only 12% overall. The inclusion of the Hispanic subset in our LUMINA cohort is probably not the explanation for this finding, since high frequencies of musculoskeletal damage have been reported for cohorts consisting solely of Hispanic patients (as well as for cohorts consisting solely of African American and Caucasian patients), and the frequency of musculoskeletal problems did not differ very much among ethnic groups in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…The positive association with older age has been consistently reported in other studies (7,40,45); it probably reflects confounding by comorbidities which increase with age, given the fact that the SDI does not differentiate between damage resulting from lupus and its treatment or damage resulting from other comorbidities. Separate analyses will be needed to evaluate whether comorbidities might be part of the explanation.…”
Section: Discussionsupporting
confidence: 61%
“…Risk factors for damage identified in adult patients with SLE include older age at diagnosis (30,32,33,36), longer duration of SLE (32,35,36), African Caribbean or Asian ethnicity (30,35), lower level of education (35), higher disease activity at diagnosis (32,33,36), greater overall activity during disease course (31,34), and cumulative and high-dose prednisone (37). By means of multivariate logistic regression analyses, we found that the presence of NPS involvement at diagnosis, a longer duration of SLE, and a greater number of intravenous cyclophosphamide pulses were the strongest determinants of cumulative organ damage in our cohort of juvenile-onset SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found a lower prevalence of serositis in Chinese patients at diagnosis, but no difference in the prevalence of discoid lupus. A study of 80 patients including 9 Asians found a higher prevalence of renal and neuropsychiatric damage (measured using the Systemic Lupus International Collaborating Clinics/ACR Damage Index) among Asian as compared with Caucasian SLE patients (11). Our larger, population-based study supports this trend toward a higher risk of developing proteinuria and CNS involvement in Chinese patients and strengthens the validity of this finding by showing that this trend persisted after adjusting for the influence of demographic, socioeconomic, disease-related, and therapy-related variables.…”
Section: Discussionmentioning
confidence: 99%